2017
DOI: 10.1074/jbc.m117.784702
|View full text |Cite
|
Sign up to set email alerts
|

Axodendritic sorting and pathological missorting of Tau are isoform-specific and determined by axon initial segment architecture

Abstract: Subcellular mislocalization of the microtubule-associated protein Tau is a hallmark of Alzheimer disease (AD) and other tauopathies. Six Tau isoforms, differentiated by the presence or absence of a second repeat or of N-terminal inserts, exist in the human CNS, but their physiological and pathological differences have long remained elusive. Here, we investigated the properties and distributions of human and rodent Tau isoforms in primary forebrain rodent neurons. We found that the Tau diffusion barrier (TDB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(171 citation statements)
references
References 67 publications
5
166
0
Order By: Relevance
“…This suggests either a selective vulnerability of the distal axonal segment, or protection against tau misfolding in proximal axonal regions. The region of the axon initial segment has been shown to act as a barrier for select isoforms of tau proteins, potentially due to increased microtubule dynamics in this area 46,47 , which may play a role in the lack of retention of misfolded tau within this region. However, it is clear that misfolded tau is able to cross this barrier and cause distal axon pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests either a selective vulnerability of the distal axonal segment, or protection against tau misfolding in proximal axonal regions. The region of the axon initial segment has been shown to act as a barrier for select isoforms of tau proteins, potentially due to increased microtubule dynamics in this area 46,47 , which may play a role in the lack of retention of misfolded tau within this region. However, it is clear that misfolded tau is able to cross this barrier and cause distal axon pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Both intrinsic features of tau and extrinsic mechanisms may contribute to its dendritic and post-synaptic recruitment. Intrinsic properties of tau include isoform composition, since 2N tau showed a higher propensity for sorting into the somato-dendritic compartment, as compared to other tau variants (Zempel et al, 2017). Furthermore, a truncated tau variant lacking the MTRs after amino acid 255 did not distribute to dendritic compartments in cultured neurons and in transgenic mouse brains (Ittner et al, 2010).…”
Section: Regulatory Pathways Of Dendritic/post-synaptic Tau Localizationmentioning
confidence: 99%
“…The AIS was shown to limit the amount of tau relocalizing from axon to soma (Li et al, 2011). This retrograde diffusional restriction of tau may be governed by several protein-protein interactions of tau with AIS complexes (such as ankyrinG/EB1, GSK3b) (Zempel et al, 2017). Furthermore, post-translational modifications may affect axonal enrichment of tau as acetylation regulates tau sorting at the AIS in cultured neurons (Tsushima et al, 2015).…”
Section: Polarized Neuronal Distribution Of Taumentioning
confidence: 99%
“…Hence, these findings show that activated cofilin can displace tau from microtubules, resulting not only in inhibition of tau-mediated microtubule dynamics but also tau hyperphosphorylation and tauopathy. Intriguingly, Zempel and colleagues showed that the axonal initial segment (AIS) of neurons contains a tau diffusion barrier composed of actin filaments that normally keeps tau in axons by preventing its retrograde traffic back to the soma [133]. A␤ oligomer-induced activation of cofilin at the AIS was found to dissolve the tau diffusion barrier, which allows missorting of tau to somatodendritic compartments [133].…”
Section: Cofilin In Tauopathymentioning
confidence: 99%